PENERIMAAN AUDITOR TERHADAP PENYIMPANGAN PERILAKU AUDIT MELALUI PENDEKATAN KARATERISTIK PERSONAL AUDITOR - Mila Susanti; Bambang Subroto (Jurnal Ilmiah Mahasiswa FEB, 2014)
This research aimed at examining the effect of personal characteristics of auditors toward acceptance of  dysfunctional  auditor  behavior.  Samples  of  this  research  were  auditors  in  East  Java  who  have experience working as an auditor for at least one year and ever did a general audit of the financial statements of the company. Setting those criteria, 110 auditors met the criteria to be taken as samples of this research. The research data collection was conducted by means of questionnaire. The results showed that the auditor's acceptance of dysfunctional audit behavior is not affected by external locus of control. Improving employee’s performance led to an increase in the auditor's acceptance of dysfunctional behavior, while decreasing turnover intentions lead to an increase in the auditor's acceptance of dysfunctional behavior. The results also revealed that turnover intention is affected by the external locus of control, employee’s performance and organizational commitment. In addition, it can be concluded that employee performance and organizational commitment is not affected by an external locus of control.   Keywords:Acceptance  of  dysfunctional  auditor  behavior,  external  locus  of  control,  employee’s performance, turnover intention, organizational commitment